Staged Multimodality Treatment of a Large Ruptured Fusiform Supraclinoid Internal Carotid Artery Aneurysm: Microsurgical Clip.assisted Endovascular Coiling - Dale Ding (Journal of Neurosciences in Rural Practice, 2017)
In the contemporary era of aneurysm management, large fusiform aneurysms presenting with subarachnoid hemorrhage (SAH) remain particularly challenging lesions to successfully manage. We describe a staged, multimodal treatment strategy for a 71-year-old patient who presented with a large ruptured fusiform aneurysm of the supraclinoid internal carotid artery (ICA) and a fetal posterior communicating artery which originated from the inferomedial aspect of the aneurysm. In the first stage, we performed a partial microsurgical clip reconstruction of the fusiform aneurysm and secured its rupture site, which was identified intraoperatively. This left two residual saccular components of the aneurysm, which were targeted with endovascular coiling in the same hospitalization after the patient had convalesced from the SAH and was beyond the vasospasm window. We believe that this combined approach of clip-assisted coiling can be employed instead of endovascular flow diversion or microsurgical bypass for appropriately selected patients with ruptured fusiform ICA aneurysms.